Pengaruh Penggunaan Question Card sebagai Media Pembelajaran terhadap Hasil Belajar PAI Kelas V SD N 01 Ulak Karang Selatan - Alwavi Nursyafri; Alfurqan Alfurqan (ALSYS, 2025)
This study is motivated by the suboptimal use of learning media in the subject of Islamic Religious Education and Character (PAI & BP) at SD Negeri 01 Ulak Karang, where teachers predominantly rely on textbooks and student worksheets (Lembar Kerja Siswa, LKS) as the main sources. Learning media, which should support engaging and interactive learning processes, are rarely used due to limited school facilities, resulting in low student enthusiasm and achievement. Data show that the learning mastery rate of Grade V D students is only 44%, far below the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal, KKM). This research adopts a quantitative approach with a quasi-experimental design, involving experimental and control groups. The research instruments consisted of questionnaires and learning achievement tests (pre-test and post-test). Data analysis indicates that the data are normally distributed (significance > 0.05), homogeneous (F calculated < F table), linear (significance > 0.05), and free from heteroscedasticity symptoms (significance > 0.05). Hypothesis testing shows significance < 0.05, indicating a significant effect of using the Question Card medium on students’ learning outcomes. In conclusion, Question Card media contributes positively to improving learning outcomes, particularly in the topic “Exemplary Leadership of the Khulafaur Rasyidin” for Grade V D students at SDN 01 Ulak Karang Selatan.